Optimization of pretreatment of jatropha oil with high free fatty acids for biodiesel production - Suwito, Supriyono (2012)
A central composite rotatable design and response surface methodology were used in order to investigate the individual and combined effects of the ethanol-to-oil ratio, H2SO4 concentration, temperature and time of reaction on the reduction of free fatty acid (FFA) in jatropha oil. A quadratic polynomial model relating the reaction variables with FFA reduction was developed, presenting a good coefficient of determination (R2= 0.893). For reducing FFA to less than 1%, the optimal combination was found to be 0.62 v$v–1 ethanol-to-oil ratio (14.9 v$v–1 ethanol-to-FFA ratio), 1.7% v$v–1 H2SO4 concentration,and 79 min reaction time at a reaction temperature of 54°C. These results are of great relevance to maximize methyl esters formation by transesterification using an alkaline catalyst.